Desastres naturais relacionados com tendências de precipitação no Espírito Santo - Roza, Mariza Pereira de Oliveira (2021)
The occurrence of natural hazards is related to extreme precipitation events that happen in a context of changes in atmospheric flow. Current and future climate extremes have adverse impacts on natural, urban and rural systems. Hazards triggered by extremes of precipitation pose major social challenges in a range of sectors, even more so in climate change scenarios. If associated with changes in land use, this relationship becomes even more complex, especially in places with complex relief, such as the case of the state of Espírito Santo, Brazil. Therefore, it is necessary to know the relationship between these factors so that mitigation measures for the negative impacts of rains on the Espírito Santo hydrographic basins are adopted and for the planning and management of these basins to be carried out. The aim of the present study was to detect recent trends in the pattern of precipitation indices for the state of Espírito Santo. In addition, we sought to associate the records of natural hazards and the evolution of changes in land use with the observed trends. The study was carried out in Espírito Santo, southeast region of Brazil. Daily rainfall data pertaining to 77 rainfall stations with historical series over 40 years were used to analyze the detection of climatic trends in different precipitation indices. Information was gathered on the records of natural hazards in the national territory that occurred from 1991 to 2020, as well as data on land use for 1985, 2002 and 2019. Historical series were established by means of the RClimDex software for each rainfall station. of some indicators of precipitation extremes. To detect trends, the Mann-Kendall (MK) test was used. The Sen estimator was applied to estimate the linear rate of change and the Pettitt test to detect abrupt change points in the indicators' time series. Qualitative analyzes of the results were also carried out, based on scientifically based information found in the literature, to relate disaster and land use data with the results of precipitation trends. In general, in the North Coast and Northwest mesoregions, trends of reduced rainfall were found, with occasional trends of increases. The occurrence of disasters such as droughts and droughts can be aggravated in these mesoregions, mainly due to the significant increase in agricultural activity. The Central and Southern mesoregions were characterized by showing increasing trends in extreme precipitation events, which justifies the high occurrence of floods and heavy rains. Points of reduction of mild rainfall were also detected in the water recharge regions, which can cause water supply problems, especially in areas with considerable increases in urban infrastructure, such as in the Metropolitan Region of Vitória, in the Central mesoregion. It can be suggested that forest restoration, as long as it is carried out prioritizing locations suitable for the purpose they intend, can mitigate the negative socio-economic and geo-environmental effects observed.